Market Reaction to the Filing of Antitrust Suits: An Aggregate and Cross-Sectional Analysis - Garbade, Kenneth D.; Silber, William L.; White, Lawrence J. (The Review of Economics and Statistics, 1982)
Kenneth D. Garbade, William L. Silber, Lawrence J. White, Market Reaction to the Filing of Antitrust Suits: An Aggregate and Cross-Sectional Analysis, The Review of Economics and Statistics, Vol. 64, No. 4 (Nov., 1982), pp. 686-691